1999
DOI: 10.1139/g99-066
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation inHordeum spontaneumpopulations

Abstract: Populations of wild barley, Hordeum spontaneum (C. Koch), originating from 10 ecologically and geographically different sites in Israel, were assessed for genome size. Measurements were obtained by flow cytometry using propidium iodide staining. Genome sizes ranged from 9.35 to 9.81 pg. Variance analysis indicated a significant difference between populations. Genome sizes were positively correlated with mean January temperature. Our results corroborate previous findings of intraspecific variation in genome siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Hordeum spontaneum, where genome size for populations representing wide ecological and geographical differences were measured, statistically significant variation up to 5% was found (Turpeinen et al 1999). This is also the case of Armeria maritima in which genome size variation of 7% was related to geographic origin (Vekemans et al 1996).…”
Section: Resultsmentioning
confidence: 78%
“…Hordeum spontaneum, where genome size for populations representing wide ecological and geographical differences were measured, statistically significant variation up to 5% was found (Turpeinen et al 1999). This is also the case of Armeria maritima in which genome size variation of 7% was related to geographic origin (Vekemans et al 1996).…”
Section: Resultsmentioning
confidence: 78%
“…It is becoming more and more evident, however, that genome size varies according to the population and even the individual concerned, and depends on various exogenous factors, the main effects of which seem to be the mobilization and increase in the copy number of transposable elements (2,7,32). Various correlations between genome size and latitude, altitude, temperature, light (9,12,13,33), developmental rate (5), etc., are well documented, especially across species. Because the environment in which an organism grows seems to influence DNA content (6), it is concluded that genome size variation is an adaptation to changing environment.…”
Section: Discussionmentioning
confidence: 99%
“…(10,11) and environmental conditions (altitude, latitude, temperature, etc.) (12,13) have suggested that natural selection could be involved in regulating genome size, although a change in size is primarily due to the genome's tolerance for repeated sequences (5) and its ability to mobilize them (14). Intra-species variation in genome size has also been shown to be associated with environmental conditions in plants, and seems to involve mobilization of some transposable elements in plants (15), Drosophila (14,16), and pocket gophers (17).…”
mentioning
confidence: 99%
“…The hybrid of male C. pandurata × female C. rumphii has a length of 2,85 ± 0,14 µm, and the hybrid of female C. pandurata × male C. rumphii has a length of 2,50 ± 0,10 µm with length ratio 1,08 ± 0,05 µm to 1,23 ± 0,07 µm. Genome size can affect the cellular parameters, such as cell size, and nucleotypic effects can have an impact on important characteristics such as growth and yield (Turpeinen et al 1999;Walker et al 2006). Truta et al (2013), states that the karyotype with metacentric and submetacentric chromosome types are considered primitive and least developed, because they are not supported restructuration and significant genetic rearrangements during evolution.…”
Section: Resultsmentioning
confidence: 99%